"Social Networking Stakeholders in Rural Development Community Based Tourism (Community Based Tourism) in Puton village, Bantul Regency" - Oktiva Anggraini (International Conference on Industrial Revolution for Polytechnic Education, 2019)
This study aims to identify social networks of stakeholders formed insupporting the development of Puton village tourism. Research design wasdescriptive qualitative, data collection techniques: in-depth interview; Literaturestudy, observation and FGD. Data analysis techniques with data reduction stages,data presentation and conclusions.The results showed that in the management of Puton tourist village, a network oftourism stakeholders a key driver for economic growth in the local area. Networksmay include hospitality, agencies, higher education institutions, private sector andNGOs. The forms of cooperation that exists include: empowerment, research,community service, patnership, continuous field trips, advocacy and CommunityService Program. In addition, active managers to promote through social medianetworks. Puton village hamlet Puton able to realize the vision of "Green Puton Self"implemented. It is thanks to the synergy of the community to work together intourism management and nurturing leadership and visionary.The networking will facilitate the stakeholders gain access to information about thefield of tourism. Local communities in synergy with the network of stakeholders cancontribute significantly and provide improved quality of life in society. Multifiereconomically-effect has been felt even institutional strengthening materialized.Posdaya and a number of traditional arts community is formed, live well maintained.With the election of the hamlet Ontoseno Posdaya Puton won national competitionsdemonstrate the success of local institutionalization. Other non-physicalmanifestation in the form of increased cooperation at the local, national andinternational acquired the hamlet.The conclusion showed stakeholder network Puton travel in the hamlet of developingthanks to the leadership and synergy society. Recommendations from this study,internet applications in the development of rural tourism cooperation networkmanagement Puton must be optimized again so that the website has an important roleas a bridge between producers and local tourism potential of tourism in providingservices to consumers / visitors. Although travel managers are faced with thepreparation of tourist packages attractive, flexibility and diversity should remainnuanced travel packages local wisdom.